The Virtual Events of Stakeholder Jatim Fest Preferences on Social Presence Approach - Ambulani, Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Virtual events have become increasingly popular during the Covid-19 pandemic and continue to be developed even as gathering restrictions have been relaxed. This research aims to determine the preferences of stakeholders in the Jatim Fest 2023 exhibition for virtual events. The research focuses on understanding participants' experiences in virtual exhibition events through the social presence theory approach. The research method used is a qualitative approach using interviews and observations. The results show that physical interaction and social presence in exhibitions provide a better sensory product experience to support sales transactions. On the other hand, participants remain actively engaged virtually through their respective social media channels without using virtual exhibition showcases provided by the organizers. This study highlights that in hybrid exhibitions, the virtual event model is not as popular and cannot yet replace the experience of physical (offline) exhibitions.